The Criminal Addict: Canadian Radio Documentary Discourse, 1957–1969. (June 2014) - Boyd, Susan
This article examines early Canadian Broadcasting Corporation radio documentaries on drugs and addiction from 1957 to 1969. Socio-historical and discourse analyses were applied to radio documentaries in this study. This article highlights how discourse about "criminal addicts" is related to conceptions of drugs, addiction, criminality, drug treatment, people who use criminalized drugs, and the professionals who regulate them. In this article, I argue that the lack of public drug treatment in Canada during this period is related to the social concept of the addict as a criminal first and a person addicted second. In addition, the diverse voices of people who used criminalized drugs such as heroin — that is, those most affected by drug prohibition and criminal addict discourse — were a clear thread of resistance throughout the study sample. In conclusion, I discuss briefly how the notion of the criminal addict has endured in Canada.